(untitled) (Papeles, 2021)
In the COVID-19 era, the traditional classroom was replaced by the electronic whiteboard, revealing a gap between academic, professional, and work training. The goal of this project was to answer this question: Are there significant differences between the knowledge management published in the literature regarding to the observations of the present study? To answer this question, a qualitative exploratory study was carried out with in-depth interviews and discourse analysis of three participants in a professional training network. The categories of training, knowledge, innovation, and entrepreneurship were established as axes of the training agenda. A structure of categories and indicators was found that explain the differences between the training models. In relation to the literature consulted that highlights the transfer of knowledge between actors, the importance of technologies, devices, and networks for establishing compatibility between training demands and institutional and organizational resources is discussed in both, the checked literature, and the present study.